Perkembangan Publikasi Ilmiah Makanan Halal di Negara Asia Analisa Bibliometrik: Penelitian Tahun 2001-2022 - Alfi Aulia; Muhammad Ruslianor Maika (ITB AAS INDONESIA Surakarta, 2023)
This study aims to find out the development of scientific publications related to the topic of Halal Food. Researchers used quantitative methods with bibliometric analysis. This research was conducted by searching through the Scopus database. id and use the keyword